Cofactor‐Free Light‐Driven Whole‐Cell Cytochrome P450 Catalysis1. Issue 3 (27th November 2014) - Park, Jong Hyun; Lee, Sahng Ha; Cha, Gun Su; Choi, Da Som; Nam, Dong Heon; Lee, Jae Hyung; Lee, Jung‐Kul; Yun, Chul‐Ho; Jeong, Ki Jun; Park, Chan Beum
Abstract Cytochromes P450 can catalyze various regioselective and stereospecific oxidation reactions of non‐functionalized hydrocarbons. Here, we have designed a novel light‐driven platform for cofactor‐free, whole‐cell P450 photo‐biocatalysis using eosin Y (EY) as a photosensitizer. EY can easily enter into the cytoplasm of Escherichia coli and bind specifically to the heme domain of P450. The catalytic turnover of P450 was mediated through the direct transfer of photoinduced electrons from the photosensitized EY to the P450 heme domain under visible light illumination. The photoactivation of the P450 catalytic cycle in the absence of cofactors and redox partners is successfully conducted using many bacterial P450s (variants of P450 BM3) and human P450s (CYPs 1A1, 1A2, 1B1, 2A6, 2E1, and 3A4) for the bioconversion of different substrates, including marketed drugs (simvastatin, lovastatin, and omeprazole) and a steroid (17β‐estradiol), to demonstrate the general applicability of the light‐driven, cofactor‐free system.